UJI AKTIVITAS TITER ANTIBODI AYAM PETELUR DAN PASCA VAKSINASI NEWCASTLE DISEASE INAKTIF - Faramitha, Ikhfina Dhea; Komala, Oom; Syamsidar, . (Universitas Pakuan, 2024)
Laying hens in Indonesia are outstanding and potential commodities. However, Newcastle Disease (ND) is one of the risks that must be faced. Now vaccination is chosen as one of the strategies to prevent ND. This paper aims to examine the effect of inactivated ND vaccine from Lentogenic and Velogenic strains on the increase in antibody titers of laying hens. To find the antibody titer value, the Hemagglutination Inhibition (HI) test method is used with serum sampling time before vaccination, 4th week, 6th week, 8th week, and 10th week post-vaccination. Meanwhile, to see the significance of the difference in titers at each time, a statistical analysis was carried out using the Paired Sample T-test. From this analysis, it is known that the Lentogenic strain has the highest significance at week 8 post-vaccination with a value of 1779.20 compared to 380.80 before vaccination. Meanwhile, the Velogenic strain had the highest significance at week 4 post-vaccination with a value of 1753.60 compared to 143.60 before vaccination. So it can be concluded that the Inactivated ND vaccine is effective in stimulating the formation of protective antibodies to fight against the ND virus attack.